2015
DOI: 10.1002/stem.2194
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase-A Inhibition Is Sufficient to Support Human Neural Stem Cells Self-Renewal

Abstract: Human pluripotent stem cell-derived neural stem cells offer unprecedented opportunities for producing specific types of neurons for several biomedical applications. However, to achieve it, protocols of production and amplification of human neural stem cells need to be standardized, cost effective, and safe. This means that small molecules should progressively replace the use of media containing cocktails of protein-based growth factors. Here we have conducted a phenotypical screening to identify pathways invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…All the results reveal that PKA phosphorylates Ctnnb1 and Gsk3β and plays a key role during NSC differentiation. Interestingly, inhibition of PKA is sufficient to maintain undifferentiated human NSC in vitro , which is consistent with our results. PKA activity may play a core role in controlling self‐renewal and differentiation of NSC.…”
Section: Resultssupporting
confidence: 92%
“…All the results reveal that PKA phosphorylates Ctnnb1 and Gsk3β and plays a key role during NSC differentiation. Interestingly, inhibition of PKA is sufficient to maintain undifferentiated human NSC in vitro , which is consistent with our results. PKA activity may play a core role in controlling self‐renewal and differentiation of NSC.…”
Section: Resultssupporting
confidence: 92%
“…Reprogramming of somatic cells into iPSC being potentially responsible for induction of epigenetic and imprinting alterations that could bias the study of gene regulation ( Pick et al, 2009 , Urbach et al, 2010 , Lister et al, 2011 ), the primary drug screening was conducted using neurons differentiated from the control hESC line SA001. The 202 compounds were screened in 4 biological replicates at one concentration determined for each compound based on data from the literature or from our own previous findings ( Boissart et al, 2013 , Georges et al, 2015 ). This primary drug screening identified 29 primary hits that increased SHANK3 mRNA content by at least 30% as compared to DMSO-treated cells and with a deviation from the DMSO mean of more than 2 σ ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15) that are differentiated into neurons to study the effect of HGPRT deficiency. We previously showed that such neurons may be instrumental to identify potentially therapeutic pharmacological compounds using automated high-throughput drug screening coupled with image-based high-content analysis (16)(17)(18). In the current study, we show that LND cells demonstrate pathological changes during key steps of the differentiation of human pluripotent stem cellderived (PSC-derived) neural stem cells (NSC) into cortical neurons.…”
Section: Introductionmentioning
confidence: 67%